The prevalence of obesity among adult population and its association with food outlet density in a hilly area of Uttarakhand - Yashneel Singh Rautela; B Venkatashiva Reddy; Amit Kumar Singh; Arti Gupta (Journal of Family Medicine and Primary Care, 2018)
Background: The rising burden of obesity is a threat to both developed and developing countries. Obesity is a killer lifestyle disease. Different aspects of the local environment play a key role in the occurrence of obesity. The present study was conducted to determine the prevalence of obesity among adult, its associated factors, and its relationship with retail food outlet density in Srikot, Uttarakhand. Materials and Methods: This study was a community-based cross-sectional study, carried out in Srikot, Uttarakhand, in 2016 among 155 adults systematically sampled, aged above 20 years. A semi-structured pretested questionnaire was used to interview the participants, and anthropometry measurements were done. The details regarding the geographic location and count of outlets were carried out. Obesity was considered body mass index ≥25 kg/m2. Results: In the present study, 61.3% were females. The mean age of the study participants was 38.3 (±13.6) years. The prevalence of overweight was 14.8% and obesity was 55.5%. A total of 92.9% of the study participants reported consumption of junk food. On mapping the study area, it was found that the total number of food outlets were 116. It was found that density of any food outlet per study participant was 0.7. Conclusion: The Srikot in Uttarakhand is in an early stage of urbanization as evident from the burden of obesity, and this might worsen by prevalent outlet density of food in the environment.